(untitled) (The Geographic Base, 2023)
This study attempts to analyze the spatial distribution of settlement patterns of Pokhara Metropolitan City. The objective of the study is to assess the effect of altitude and slope on settlement pattern. The settlement areas of Pokhara Metropolitan City are categorized into three classes of altitude and five classes of slope degree. The study has used the spatial technique based on the Nearest Neighbor Index and ArcGIS and MS Excel application software. Point based settlement data were collected from the Department of Survey, Nepal and topographical data was collected from ASTER DEM satellite platform. The result shows that the settlement pattern in the Pokhara valley is that settlements are densely concentrated in the flat terrain, especially in 1-10 wards, and support infrastructure development with commercial activities. Conversely, as the elevation increases towards the surrounding hills, the settlement pattern become tendency towards more dispersed. The pattern based on altitude, below 1200 meters reveals dispersed settlement pattern, whereas above revels random. Similarly, the pattern of slope degree indicates dispersed to more disperse according to increase of slope degree.